Determination of learning needs of patients with pace maker - Nasrin Imanzadeh (Iran University of Medical Sciences, 1998)
A field study was made to investigate the learning needs of patients with pacemaker in Shahid Rajaii Heart Hospital's out-patient clinic (1994). A total of 60 patients with pacemaker were selected sequentially from the total population that had a pacemaker and attended the out-patient clinic in shahid Rajaii Hospital. The subjects met the criteria for participating in this study. The tool was a questionnaire consisting of three parts that would gather the information needed to cover the purposes of this study. The first part posed 22 questions regarding the subject's personal characteristics, the second part with 20 questions covered information about self-care in patients with pacemaker and the third part examined the respondents' orientation with pacemaker site, its care, improper functioning and related warning signs, with 20 questions. The findings were presented in 32 tables. Both descriptive and inferal statistics were employed for data analysis. The mean age of the subjects was 58.68 years, the majority were married, most of them said that no previous instruction was given to them about self-care. A positive correlation was estimated between having previous information on self-care and knowledge about pacemaker placement site care, improper functioning of pace makers and related warning signs. Most of the subjects, regardless of the length of pacemaker insertion said their self -care learning needs were high, their knowledge on the care of pacemaker placement site, its improper functioning and related warning signs was satisfactory. Their level of education and learning needs were significantly correlated, but occupation was not related with those matters mentioned above. The range of pacemaker insertion and length varied, most of them had it for 1-39 months and the longer they had the pacemaker the less were their learning needs, thus a slightly reverse correlation was estimated between these two sets of variables. The fmdings also revealed that the majority of those who were better oriented to the care of pacemaker site, malfunctioning and warning signs claimed less learning needs on the subjects. Based on the findings suggestions were made for implaementing the results in nursing services and recommendations for further research were made.